The effects of led lighting on the commercial cultivation of Stevia rebaudiana / Narendren Rengasamy - Narendren , Rengasamy (2023)
Stevia rebaudiana is a perennial plant from the Asteraceae family, native to the highlands of Brazil and Paraguay. It is a high-value crop due to the strong commercial demand for its metabolites (steviol glycosides, SG) as an organic low-caloric sweetener with up to 300 times the sweetness of conventional sugar. Stevia rebaudiana a short-day plant, has a tendency for a shortened vegetative stage and early flowering when grown under a photoperiod of 12 h or less. The amount of SG in the leaves reduces by up to 50% after flowering. Given the strong commercial demand for Stevia products, and the limited supply available domestically, intense cultivation in controlled environment agriculture (CEA) systems is a viable option. Lighting energy can account for more than 70% of the total electrical energy used in a CEA system while the CEA system itself can consume up to 100% more electrical energy compared to a conventional greenhouse. This study included three experimental set-ups, using four different lighting strategies. All artificial lighting systems used high powered light emitting diodes (LED). In the first experiment, the plants were grown under Red + Blue light with photoperiods of 8, 12 or 16 hours (8H, 12H, 16H) and an intermittent photoperiod of 5 hours 20 minutes (16HI) per 8 hours (for a total of 16 hours each day). A control sample was grown under natural sunlight and photoperiod (12 hours) in the climate-controlled greenhouse (GH). In the second experiment, the plants were grown under 6 different spectral compositions that had a base Red + Blue (RB) spectra. The control plants were grown under pure RB spectra while others were grown under RB supplemented with Far Red (FR), Ultraviolet A (UVA), Blue (BR), Green (GR), FR+UVA+GR (FS). In the third experiment, varying fractions of UV-A and green light in addition to the base RB was used. Two treatments with green fractions (GR1 & GR2), two treatments with UVA (UV1 & UV2) and two treatments that had both (UVGR1, UVGR2). A separate set of plants were grown under RB and natural sunlight before being transferred to GR2, UV2, UVGR2, and monochromatic light treatments of blue, green and UVA, for 3 and 10 days before harvest. Plants grown under the UVGR1 had the highest dry leaf biomass accumulation of 4.75 g plant-1 (P<.05). UVA had the highest metabolite (ST + Reb A) concentration of 27% (P<.05) while plants grown under sunlight had a mean SG concentration of 15%. UVGR1 had the highest metabolite yields and energy use efficacy of 1.05 g plant-1 and 30.24 mg kWh-1 (P<.05) respectively. In terms of productivity, the GR1 spectral composition was the most productive, producing 18.7 (P<.05) milligrams of ST + Reb A compounds for every mol of light used. Overall, this study demonstrated the effects of different lighting strategies on the productivity and energy use efficacy of indoor grown Stevia rebaudiana. It was observed that strategies that used spectral composition with green and UV-A were more productive and had higher efficacies compared to photoperiod manipulation, or the use of pre-harvest lighting.